2022
DOI: 10.2147/dmso.s359742
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hypertriglyceridemic-Waist Phenotype and Chronic Kidney Disease in Patients with Type 2 Diabetes: A Cross-Sectional METAL Study

Abstract: The aim of this study was measuring the association between the hypertriglyceridemic-waist (HTGW) phenotype and chronic kidney disease in a large type 2 diabetes population. Methods: A total of 4254 diabetic patients from the cross-sectional Environmental Pollutant Exposure and Metabolic Diseases in Shanghai (METAL) study were enrolled. The hypertriglyceridemic-waist (HTGW) phenotype was defined as the presence of an elevated waist circumference (WC) and elevated triglyceride (TG) concentration. Chronic kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
1
1
Order By: Relevance
“…27 Other factors including insulin resistance, oxidative stress and genetics may also affect to different degrees. 28 Consistent with previous studies, [10][11][12] our data showed that the use of ACEI/ARB was not independently correlated with renal outcome in ORG patients. Except for the influence of possible body weight gain in the follow-up time, the occurrence of aldosterone escape may explain the result.…”
Section: Discussionsupporting
confidence: 91%
“…27 Other factors including insulin resistance, oxidative stress and genetics may also affect to different degrees. 28 Consistent with previous studies, [10][11][12] our data showed that the use of ACEI/ARB was not independently correlated with renal outcome in ORG patients. Except for the influence of possible body weight gain in the follow-up time, the occurrence of aldosterone escape may explain the result.…”
Section: Discussionsupporting
confidence: 91%
“… 10 The result of CKD-related vascular complications was consistent with Yan’s study. 25 However, we did not find an association between HWP and DR.…”
Section: Discussioncontrasting
confidence: 79%
“…26,27 Visceral fat cells stimulate the secretion of inflammatory factors such as interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), and adipokines, which lead to the production of reactive oxygen in arterioles. 25 Therefore, pro-inflammatory cytokines and reactive oxygen species produced by obesity can directly affect endothelial cells, leading to endothelial dysfunction. 28 In our study, there was an age difference in the result between HWP and vascular complications of diabetes.…”
mentioning
confidence: 99%
“…Of those 20 full-text articles, seven were excluded for the following reasons: six articles did not have data on the outcome of interest, and one article was not in the English language. Therefore, the remaining 13 articles, [16][17][18][23][24][25][26][27][28][29][30][31][32] which together had 113,019 participants, were included in the analyses (Fig. 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%